SOLIDIFICAÇÃO DE AÇOS INOXIDÁVEIS FUNDIDOS DA CLASSE CF-8M: EVOLUÇÃO MICROESTRUTURAL - Ferreira, Dannilo Eduardo Munhoz (2015)
Austenitic stainless steels have a wide range of applications and are widely used in applications requiring high corrosion resistance, and CF-8M class are generally submitted to corrosive environments in liquid media. The microstructure of these steels has an austenitic matrix and a variable amount of delta ferrite resulting from the casting process, which is affected by process variables like cooling rate, and chemical composition of the melt. In this work were characterized four alloys of CF-8M class austenitic stainless steels. The chemical compositions differ only in chromium and nickel contents in order to generate different amounts of chromium equivalent (Creq) and nickel equivalent (Nieq) according to the Schoefer diagram with ratio Creq/Nieq ranging between 0.95 and 1.35. The variation in the value of the ratio Creq/Nieq aims to observe the influence of chemical composition on solidification mode and the phase transformations during processing of the alloy. The alloys were cast in the form of pins which samples were removed for characterization. The microstructural characterization of alloys was made with the techniques of optical microscopy with image analysis, Field emission microscope (SEM / FEG) with energy dispersive X-ray spectrometry and electron backscatter diffraction (EDS / EBSD) to compositional map. The ferritoscopy technique, EBSD phase map and XRD were used to determine the ratio between phases. Thermal analysis by DSC determined the solidification interval for alloys in the study and phase transformations resulting during cooling to room temperature. The results showed that alloys 1, 2 and 4 solidify with FA mode, as expected. The alloy 3 showed a corresponding microstructure of eutectic/peritectic solidification, not presented in any of the existing diagrams in the literature. The measures of δ-ferrite fraction for all leagues were valid for the values proposed by Schoefer diagram. The examination of the micrographs of alloys shows the variety of microstructures that a CF-8M steel can display only altering its chemical composition. The EDS/EBSD maps showed a higher segregation of alloying elements between the phases for alloys 1, 2 and 4, due to the solidification mode and further transformation in solid state. The alloy 3 showed a smaller difference in composition between phases and less variation within the same phase, which features a eutectic/peritectic solidification. The comparison between the different regions of the samples presented variation in the fraction and morphology of ferrite. The range of solidification of the four alloys in the study was within a maximum level of 4 ° C, expected to solidification with ferrite as the first phase to form from the liquid. It was observed for the alloys to solidify with FA mode a phase transformation in the solid state in the range 1320 °C to 1340 °C, corresponding to γ transformation. The energy of this transformation is inversely proportional to the amount of ferrite observed in the final microstructure of alloys.